Multi Metode Dan Multi Perspektif Konstruk Budaya Kesenangan (Indulgence) Terhadap Pembelian Impulsive Online Dengan Machine Learning - Devano Ramadhan, Rendhika; Abadi, M. Fairuz; Fernando M S, Manuel; Yudiarso, Ananta (Jurnal Ilmiah Psyche, 2024)
This study discusses impulse buying behavior among university students in Indonesia, with a particular focus on the influence of online shopping platforms. There is an increasing trend of online shopping and its significant impact on consumer behavior, especially among young adults. This research utilizes a mixed methods approach, combining secondary data and qualitative interviews to collect comprehensive and detailed data. The results show that emotional triggers, such as stress and excitement, as well as social influences, including peer pressure and social media, play an important role in driving impulse buying. Furthermore, it is found that promotional offers, free shipping, and attractive discounts are the main factors that contribute to this behavior